Pathomorphologic and immunohistochemical changes in brain at brain strokes in conditions of blood brain barrier permeability disorder - Tertyshny, S.I.; Gulenko, V.E. (Pathologia, 2013)
Pathomorphologic methods show that mainly CD8 and CD68 immune cells are accumulated at brain strokes which are based on microcirculation disorders with increased permeability of blood brain barrier. Accumulation of immune cells is accompained by inflammation and it can play an important role in pathogenesis of cerebral-vascular diseases.